Optimalisasi Auto Dosing Cement Additive Berbasis PLC-SCADA dengan Kendali Closed-Loop pada Finish Mill - Affan Bachri; Moch Syafi Uddin; Eko Wahyu Santoso; Abd Kadir Mahamad (Nucleus Journal, 2026)
PLC is a programmable logic control system that uses a microprocessor as the main controller and is widely applied in industrial automation processes such as monitoring and controlling production machinery. The system is equipped with input and output devices that interact with external components such as buttons, sensors, actuators, and other hardware devices. This technology has been implemented in various fields, including cement production processes. In this study, the programmable logic controller was used to modify the auto dosing system for cement additive with the aim of improving dosing accuracy, enabling real-time monitoring, and developing an auto dosing system capable of adapting to changes in feed material. The previous system operated manually and relied heavily on operator intervention, resulting in inconsistent dosing performance. To overcome these limitations, a programmable logic controller-based control system integrated with a supervisory control and data acquisition system was implemented. The system applied a closed-loop control method to regulate the dosing process in order to achieve stable and consistent output. System performance was evaluated by comparing the accuracy and stability of the flow rate before and after modification. The analysis results showed that the proposed system reduced the error between the setpoint and the actual flowmeter reading from 16% to 3%, decreased flow fluctuations, and improved process stability. In addition, the system enabled centralized monitoring and reduced operator dependency, thereby improving operational efficiency.